Dow Science. Creating the Brightest Ideas in Household Products Since 1953. - Dow Chemical Company (1997)
Color print newspaper advertisement for the Dow Chemical Company is a photograph of various products DowBrands produces including Scrubbing Bubbles Bathroom Cleaner, Saran Wrap, Glass Plus, fantastik, heavy duty oven cleaner, Spray 'n Wash, Handi-Wrap and Ziploc Freezer Bags. This advertisement appeared on page 16 of the Dow Chemical Company 100th Anniversary found within section two of the Midland Daily News dated May 18, 1997.
Keywords: Dow Chemical Company; Food--Preservation; Cleaning compounds